The Potential Liquefaction in Yogyakarta and Bantul - Selvia Agustina (International Conference on Coastal and Delta Areas, 2017)
The phenomenon of liquefaction occured in Yogyakarta at the massive earthquake on May 27th, 2006. This phenomenon may be occur again because of the geological and seismic conditions in Yogyakarta that support the occurrence of liquefaction. This research aims to determine the level of liquefaction potential in Yogyakarta especially the central of Yogyakarta and Bantul. Analysis of Liquefaction potential use Youd method. The results of soil investigation shows that the type of soil in the research area is uniformly graded sand. The depth of the ground water level in October 2015 in the research area around 0,8-13,4 meters. The Attenuation function of Crouse-Mc Guire produce PGA largest value-which is about 0,23g-0,56g. The potential liquefaction in Yogyakarta is about 0 – 2,06 (very low) and Bantul is about 0 – 48. Watu is the highest potential liquefaction in Bantul. Keywords: earthquake, liquefaction, LPI